Cataract Surgery Results after Penetrating Keratoplasty - M. A. Tanash; M. A. Frolov; V. Kumar; L. T. Ababneh; A. A. Alqudah (Oftalʹmologiâ, 2022)
Objective. To compare clinical and refractive outcomes of cataract surgery by phacoemulsification and by extracapsular cataract extraction with implantation of foldable and rigid intraocular lenses in patients previously having undergone penetrating keratoplasty (PK).Patients and methods. This is a retrospective study. Medical records of all patients admitted for cataract surgery between 2010 and 2018 to the King Abdullah University Hospital (KAUH) were reviewed and medical records of patients who underwent cataract surgery after PK were analyzed. Medical records of 95 patients (58 males and 37 females; average age 40.0 ± 19.9 years) were selected. Depending upon the type of surgical technique applied, the cases were divided into two groups: first group included 60 patients who underwent cataract surgery by phacoemulsification with implantation of different foldable intraocular lenses (IOL), the second group included 35 patients who underwent cataract surgery by extracapsular cataract extraction (ECCE) with implantation of a polymethylmethacrylate (PMMA) IOL. The choice of ECCE technique with implantation of rigid IOLs was made if the endothelial cell density after PK was less than 2200 cells/mm2 and cataracts were of 4 and 5 grades to exclude additional trauma to the endothelium by ultrasound energy. Demographic and clinical data were collected. The R statistical program and SPSS were used for data analysis. The P value < 0.05 was considered statistically significant.Results. Analysis showed that PK was performed mainly due to 4 indications: keratoconus (KC) — 77 % cases, herpetic keratopathy — 7 % cases, Eye trauma — 5 % cases, previous graft rejection — 5 % cases and Stevens–Johnson syndrome — 1 % cases. The mean best corrected visual acuity (BCVA) in the first group improved from 0.40 ± 0.05 to 0.80 ± 0.05 postoperatively. The mean BCVA in the second group improved from 0.30 ± 0.05 to 0.70 ± 0.05. In the late postoperative period BCVA with foldable IOLs was higher by 0.10 ± 0.05, as compared with the results obtained with the rigid IOLs. Mean intraocular pressure (IOP) changed from 15.1 ± 4.9 before PK to 16.3 ± 5.3 after PK.Conclusion. KC was the most common indication for PK in Jordan. Results of our analysis showed that cataract surgery could be successfully performed in eyes after PK with favorable results and improvement in patients’ quality of life. Cataract surgery by phacoemulsification with implantation of foldable IOLs results in higher (BCVA) compared to ECCE with implantation of PMMA IOLs. Unless contraindicated otherwise, phacoemulsification technique with foldable IOL implantation should be given preference over ECCE with implantation of rigid PMMA IOLs in visual rehabilitation of cataract patients after PK.